Basin scale monitoring of microplastics and phthalates in sediments from the Persian Gulf and the Gulf of Makran using GIS-based algorithms: Insights towards spatial variation and potential risk assessment - Aghadadashi, Vahid; Mehdinia, Ali; Rezaei, Mahdie; Molaei, Saeideh; Seyed Hashtroudi, Mehri; Ahmadian, Fatemeh; Hamzehpour, Ali; Rahnama, Reza (The Science of the total environment, 2024)
Information on sedimentary microplastics and phthalates has been restricted to the coastal regions of the Persian Gulf and the Gulf of Makran. Our basin-wide study monitored their levels, spatial behaviors, and potential risks using GIS-based techniques. Microplastics and phthalates ranged from 5 to 75 particles/kg d.w and 0.004–1.219 μg g−1 d.w, respectively. Microplastics were in the size category of 100 μm to 3 mm, and black microfibers (< 1 mm) and high-density polymers were dominant. The total number of microplastics was between 356.333 × 1012 and 469.075 × 1012 particles in the surface sediments of the studied regions (confidence interval = 99 %). Diethylhexyl phthalate (DEHP) and Di-isobutyl phthalate contributed 88 % of detected phthalates. Significant correlations among microplastic abundance, total phthalates, and DEHP were distinguished (p < 0.05). Overall, the findings reiterated the widespread presence of microplastics and a potential link between phthalates and microplastics. Semi-variogram, cluster Voronoi polygons, and Trend analysis identified spatial outliers and major deposition sites of microplastics and phthalates and consequently outlined the localities where upcoming studies should be concentrated. A hotspot of potential risks was marked using Fuzzy logic and GIS-based algorithms in the Sea of Makran, covering an area equal to 342. 99 km2. [Display omitted] •Black fibers (0.5–1 mm) and high-density microplastics (MPs) were dominant.•The total number of MPs was between 3.56 × 1014 and 4.69 × 1014 in the studied regions.•A significant correlation existed between Diethylhexyl phthalate (DEHP) and MPs.•Di-isobutyl phthalate and DEHP contributed 88 % of the detected phthalates.•Phthalate and MP load were independent of sediment properties except for MPs <1 mm.